Ferric Sulfate and Proline Enhance Heavy-Metal Tolerance of Halophilic/Halotolerant Soil Microorganisms and Their Bioremediation Potential for Spilled-Oil Under Multiple Stresses - Al-Mailem, Dina M.; Eliyas, Mohamed; Radwan, Samir S. (Frontiers in Microbiology, 2018)
The aim of this study was to explore the heavy-metal resistance and hydrocarbonoclastic potential of microorganisms in a hypersaline soil. For this, hydrocarbonoclastic microorganisms were counted on a mineral medium with oil vapor as a sole carbon source in the presence of increasing concentrations of ZnSO4, HgCl2, CdSO4, PbNO3, CuSO4, and Na2HAsO4. The colony-forming units counted decreased in number from about 150 g-1 on the heavy-metal-free medium to zero units on media with 40–100 mg l-1 of HgCl2, CdSO4, PbNO3, or Na2HAsO4. On media with CuSO4 or ZnSO4 on the other hand, numbers increased first reaching maxima on media with 50 mg l-1 CuSO4 and 90 mg l-1 ZnSO4. Higher concentrations reduced the numbers, which however, still remained considerable. Pure microbial isolates in cultures tolerated 200–1600 mg l-1 of HgCl2, CdSO4, PbNO3, CuSO4, and Na2HAsO4 in the absence of crude oil. In the presence of oil vapor, the isolates tolerated much lower concentrations of the heavy metals, only 10–80 mg l-1. The addition of 10 Fe2(SO4)3 and 200 mg l-1 proline (by up to two- to threefold) enhanced the tolerance of several isolates to heavy metals, and consequently their potential for oil biodegradation in their presence. The results are useful in designing bioremediation technologies for oil spilled in hypersaline areas.